A numerical study of dissipative chemically reactive radiative MHD flow past a vertical cone with non-uniform mass flux - Sambath, P.; Sankar, D.S.; Viswanathan, K.K. (Zielona Góra: Uniwersytet Zielonogórski)
A computational model is presented to explore the properties of heat source, chemically reacting radiative, viscous dissipative MHD flow of an incompressible viscous fluid past an upright cone under inhomogeneous mass flux. A numerical study has been carried out to explore the mass flux features with the help of Crank-Nicolson finite difference scheme.
Keywords: free convection; finite difference; vertical cone; MHD; thermal radiation; viscous dissipation